Peer Leaders Increase Organ Donor Designation Among Members of Historically African American Fraternities and Sororities. (December 2017) - Loughery, Caitlin; Zhang, Nanhua; Resnicow, Ken; Chapman, Remonia; Magee, John C.; Andrews, Ann M.
Introduction: Health education programs can positively impact organ donor designation among African Americans, a disproportionately represented group on the transplant waiting list. Alumni chapters of historically African American sororities and fraternities are a novel setting for organ donation education and research. Research Questions: This study tested the effectiveness of a lay health advisor model to increase donor designation registrations on the Michigan Organ Donor Registry among members of Midwest alumni chapters. The secondary outcome was change in attitudes toward donation assessed by pre–post questionnaire. Design: Sorority/fraternity members were trained to deliver educational presentations during a 12-month period. Follow-up messaging consisted of tailored newsletters and e-mails. A cluster randomized design was utilized with 25 chapters (16 sororities and 9 fraternities) assigned to intervention (organ donation) or comparison (chronic disease). Results: Odds of signing up for the donor registry were 1.45 times higher for the intervention group than the comparison group. Among those identified as nondonors at baseline, the odds of signing up were 1.58 times higher for intervention than comparison. Discussion: Using lay health advisors in African American sororities and fraternities can increase enrollment in a donor registry. Alumni chapters offer a unique and viable setting for organ donation education and research; relationship building with chapter officials is key to success.